HIV and AIDS : all you need to know - Otuka, Mary G.; Kiarie, William N.; Muraah, William M. (Nairobi, Kenya : Ukweli Video Productions, 2003)
This is an educational video whose objective is to provide comprehensive, yet simplified information on HIV/AIDS. William Kiarie and William Muraah, HIV/AIDS consultants and trainers, present the basic HIV/AIDS facts and issues while Shades Classics, a youth theater group addresses the same issues through captivating music, dance, and poetry. The blend of the two approaches is a powerful tool that supports both information and behaviour change.
v. 1, pt. 1. What is HIV/AIDS. pt. 2, The origin of HIV/AIDS. pt. 3, HIV/AIDS in Africa. pt. 4, The biology of the virus -- v. 2, pt. 1. The HIV test. pt. 2, Transmission of HIV. pt. 3, HIV prevention. pt. 4, HIV/AIDS disease and treatment -- v. 3, pt . 1. HIV/AIDS, culture, and religion. pt. 2, The social and economic impact of HIV/AIDS. pt. 3, HIV/AIDS and gender. pt. 4, HIV/AIDS and children.
Summary from Videocassette container.